Relational Composition between Periodic Fluctuation and Seasonal Variation in Height Growth - Tanaka, Nozomi; Fujii, Katsunori (European Journal of Applied Sciences, 2023)
The influence of seasonal variations in height growth has been frequently discussed previously. In recent years, however, Fujii[1] has hypothesized periodic fluctuations, accordingly the variation is not from the environmental factor of season; rather, height growth is achieved with periodic variations due to genetic factors. Based on this logic, wavelet interpolation was applied to observed data values measured three times a year in this study to investigate the periodic fluctuations in height and weight growth in elementary school children, and an attempt was made to verify the periodic fluctuations from the behavior of the derived velocity curve. The longitudinal time series information on subjects’ height and weight were measured three times a year from the first to sixth grades. The data used in the analysis were for 17 boys and 11 girls. The results showed that the height growth pattern is essentially achieved with periodic fluctuations, and that there are seasonal stimulating phenomena within that periodicity. If this growth mechanism also applies to body weight, growth in body weight would occur together with increases in height, but with additional seasonal stimulating effects weight would be affected not only by genetic factors as height is, but also by seasonal environmental factors.